A educação e cotidiano escolar em São José dos Campos (1889-1930) - Roque, Zuleika Stefânia Sabino (2007)
Comprehend how the public education hás been developed in the city of São José dos Campos during the two first decades of the 20 th century has been our main objective. This period is very rich, making it possible to understand how schools began to multiply and establish a public system, similar to the one we have today. We situated São José dos Campos in the Empire-Republic transition, having as background the Politics of Public Hygiene, security, health and particularly the Education one with, when articulated, legitimated the speech in favor of cities `modernity. On behalf of Order and Progress, came the necessity to educate the former-slave, the immigrant, the people, to nationalize the country. In this manner, the way how the local press, the legislation and the memorialists made a speeches about Education, allowed us to recover what these social segments understood by Education. In this way, the schools, practically inexistent during the Empire, began to multiply with the Republic and places destined to education finally were consolidated. To search through the sources, the social sectors that constituted the social classes and to show off, conflicts of interests, the profile of who managed and frequented such places and the profile of who appropriated them were some of the questionings that we pursued with the intention to elucidate the social organization and the complexity of analysis categories of public and private. In attempt to deeply understand these politic, social and economic structures and identifying the conflicts between different groups, without missing the matching point between them, that is, the created and pursued necessity to search capability, we studied the school, its instruments, programs, customs, that is, the school s quotidian that made emerge an ideology behind those scholar experience